How to run a government so that citizens benefit and taxpayers don`t go crazy - Barber, Michael (UK, 2015)
This groundbreaking book Michael Barber draws on his wealth of experience of working for and with government leaders the world over to present a blueprint for how to run a government.
Keywords: Public administration